The Comparison and Modeling of the Driving Factors of Urban Expansion for Thirty-Five Big Cities in the Three Regions in China - Tian Guangjin; Xu Xinliang; Liu Xiaojuan; Kong Lingqiang (Advances in Meteorology)
This paper presents a national- and regional-scale urban growth model (NRUGM) of China based on panel data analysis. Through the panel analysis, population growth, road construction, salary increment per capita, and secondary industry product increment were proven to be the major driving factors for national-scale urban expansion. According to Seventh Five-Year Plan, China had been divided into three regions, Eastern China, Middle China, and Western China, by their geographic position and economic development. We studied the relationship between urban expansion and the driving factors for the three regions between 1990 and 2010 in China. The driving factors of urban expansion were different for the different regions and periods. Population growth and road construction were identified as the two major factors driving urban expansion for Eastern China. Secondary industry and economic development had become the major driving factors for urban expansion over the last twenty years in Middle China. Over the same period, for Western China, economic growth had become the major driving factor for urban expansion. Our results have significant policy implications for China. The macrocontrol of the central government should utilize different policies to adjust urban expansion in the different regions.